Möte i teaterrummet - Edlom, Suzanne (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
This article deals with how theatre happens and how meaning is created by the use and experience of theatre. I have experienced two different theatrical performances, on four different occasions, with the purpose of experience and examine the theatrical performance as an event. Four different theatre events and experiences but they all showed how the meaning sprang from the actual event, as it happened, there and then, through an encounter and exchange between the present people in the room. A sensuous and emotional co-operation which created a significant and live exchange between actors and audience. An exchange through human encounter, created by physical presence and sensuous contact.